Hake Fish Preservation Using Plant-Based Impregnated Polylactic Acid Food Films as Active Packaging - Fini Sánchez-García; Noelia D. Machado; María Tirado-Fernández; Cristina Cejudo-Bastante; Ana M. Roldán; Casimiro Mantell-Serrano; Lourdes Casas-Cardoso (Applied Sciences)
Global fish consumption has steadily increased; however, fishery products are difficult to preserve. Active packaging has emerged as an alternative to improve its conservation. In this work, fresh hake fillets were packaged in commercial polylactic acid films impregnated with olive leaf extract using supercritical CO2. The impregnation was performed at 35 °C and 400 bar for 1 h. The ABTS assay was used to determine the antioxidant activity, and migration tests were performed using food simulants A and D2 for 10 days at 5 °C. The fresh fillets were packaged in impregnated and control films and stored for 12 days at 4 °C. The microbiological, physical (drip loss, aw, pH, and color) and chemical parameters (total volatile base and trimethylamine) were analyzed. The impregnated films presented a 706 μg extract mg−1 polymer, showing a 2-fold extract release using food simulant D2 than simulant A. After hake storage using impregnated films, reduced microbial count, and drip loss, maintaining the pH stability was obtained. The color turned yellowish and no detectable olfactory presence of the extract was noted. The chemical parameters were similar in both types of films. The proposed biodegradable packaging with olive by-products preserves moisture and controls microbial growth, representing an eco-friendly alternative.